Hubungan Dukungan Keluarga Dengan Kepatuhan Pembatasan Asupan Cairan Pada Pasien Gagal Ginjal Kronik di Unit Hemodialisa - Rosa Anugrah Kusuma Dewi; Karwati; Afreani Deasy (LPPM STIKES Guna Bangsa, 2023)
Chronic Kidney Disease (CKD) is a kidney function disorder characterized by a gradual decline in the filtration rate, resulting in severe and irreversible kidney damage. In patients with CKD, the body's fluid balance will be disrupted, necessitating the use of fluids. Fluid in the body will result if the patient is unable to control his or her fluid intake. Hemodialysis patients’ health and quality of life are largely determined by their fluid compliance. Family support is one of the risk variables that can influence a patient's willingness to reduce fluid intake. The purpose of this study is to see if there's a link between family support and the need for fluid contact in kidney failure patients at avisena general hospital's hemodialysis unit. This is a quantitative research method that employs an analytical descriptive method with a cross-sectional design. The purposive sampling strategy was used to select 30 respondents for this investigation. Family support and fluid request questionnaires were employed as the research tool. Almost all of the 24 respondents (80.0 %) had good family support, and the majority of the 22 respondents (73.3 %) were obedient in restricting fluid intake, according to the findings. According to Fisher's exact test analysis, p-value = 0.002 < (0.05), there is a significant correlation between family support compliance with fluid intake restrictions in chronic kidney disease patients at the hemodialysis unit at avisena hospital. The findings of this study are likely to be utilized as a guide and foundation for future research.